2023
DOI: 10.1038/s41398-023-02365-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of brain function: role in psychiatric disorders

Abstract: Seasonality patterns are reported in various psychiatric disorders. The current paper summarizes findings on brain adaptations associated with seasonal changes, factors that contribute to individual differences and their implications for psychiatric disorders. Changes in circadian rhythms are likely to prominently mediate these seasonal effects since light strongly entrains the internal clock modifying brain function. Inability of circadian rhythms to accommodate to seasonal changes might increase the risk for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 183 publications
0
31
0
Order By: Relevance
“…𝐶𝑜𝑠𝑡 𝑓𝑢𝑛𝑐𝑖𝑜𝑛 = 𝐿𝑜𝑠𝑠 + 𝑅𝑒𝑔𝑢𝑙𝑎𝑟𝑖𝑧𝑎𝑡𝑖𝑜𝑛 𝑝𝑎𝑟𝑎𝑚𝑒𝑡𝑒𝑟 (1) In L2 or weight decay lambda is known as regularization term which is a hyperparameter whose value is changed for achieving improved results. It forces weight to decay not exactly zero but towards zero, as described in Eq.…”
Section: L1 and L2 Regularization Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…𝐶𝑜𝑠𝑡 𝑓𝑢𝑛𝑐𝑖𝑜𝑛 = 𝐿𝑜𝑠𝑠 + 𝑅𝑒𝑔𝑢𝑙𝑎𝑟𝑖𝑧𝑎𝑡𝑖𝑜𝑛 𝑝𝑎𝑟𝑎𝑚𝑒𝑡𝑒𝑟 (1) In L2 or weight decay lambda is known as regularization term which is a hyperparameter whose value is changed for achieving improved results. It forces weight to decay not exactly zero but towards zero, as described in Eq.…”
Section: L1 and L2 Regularization Techniquementioning
confidence: 99%
“…One of the most complicated organs of human body is the brain which controls all the actions of human body by receiving information from different senses and send them back for performing the appropriate action [1]. An abnormality to this organ can create serious effects on the functionality of the human body, this abnormality is well known as the brain tumor [2].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, seasonal changes directly affect the duration of daylight. Seasonal daylength fluctuations appear to affect mood and behaviour negatively and were associated with a higher prevalence of seasonal affective disorder and earlier onset of bipolar disorder (201). Here it is important to acknowledge that many of these findings are susceptible to bias due to inadequate control of confounders and the risk for an ecological fallacy – the incorrect inference about individuals based on aggregated-level data associations (202).…”
Section: Weather Patterns and Climate Changementioning
confidence: 99%
“…Additionally, impairments in the FC of the DMN were observed (210), coupled with prolonged reaction time in cognitive tasks compared with the control group (209,210). A few cross-sectional studies reported positive associations between daylength and volumes of the hippocampus, amygdala, and brain-stem – regions that exhibited seasonal variations in serotonin signalling (201), suggesting that changes in volumes of subcortical regions and neurotransmitter signalling involved in emotional regulation may be involved in the seasonality of mental disorders.…”
Section: Weather Patterns and Climate Changementioning
confidence: 99%
“…whereas depressive episodes mostly peak in early winter, and mixed episodes peak in early spring as well as in the middle of or late in the summer (Fellinger et al, 2022;Geoffroy et al, 2014;Zhang and Volkow, 2023). Few studies have focused on anxiety, sleep and substance use disorders, although these have been associated with self-reported SAD (Palmu et al, 2022;Sandman et al, 2016).…”
mentioning
confidence: 99%